Circulating U2 small nuclear RNA fragments as a novel diagnostic biomarker for primary central nervous system lymphoma. Issue 3 (6th August 2015) - Baraniskin, Alexander; Zaslavska, Elena; Nöpel-Dünnebacke, Stefanie; Ahle, Guido; Seidel, Sabine; Schlegel, Uwe; Schmiegel, Wolff; Hahn, Stephan; Schroers, Roland
Abstract: Background: Primary central nervous system lymphomas (PCNSLs) are highly aggressive tumors. Chemotherapy has improved prognosis significantly; however, early diagnosis is crucial for effective treatment. Presently, the diagnosis of PCNSL depends on histopathology of tumor biopsies. We have previously demonstrated differential expression of microRNAs in cerebrospinal fluid (CSF) samples from patients with PCNSL. Based on promising findings about circulating U2 small nuclear RNA fragments (RNU2-1f) as novel blood-based biomarkers for pancreatic, colorectal, and lung cancer, we investigated RNU2-1f in the CSF of PCNSL patients. Methods: CSF was collected from patients with PCNSL ( n = 72) and control patients with various neurologic disorders ( n = 47). Sequential CSF samples were collected from 9 PCNSL patients. RNU2-1f levels were measured by real-time polymerase chain reaction. Results: Measurement of RNU2-1f levels in CSF enabled the differentiation of patients with PCNSL from controls with an area under the curve (AUC) of 0.909 with a sensitivity of 68.1% and a specificity of 91.4%. The diagnostic accuracy was further improved by combined determination of RNU2-1f and miR- 21, resulting in AUC of 0.987 with a sensitivity of 91.7% and a specificity of 95.7%. In consecutive measurements of RNU2-1f, which were performed in 9 patients at different stages of the disease course, RNU2-1f CSF levels paralleled the course of the disease. Conclusions: Our data suggest that the measurement of RNU2-1f detected in CSF can be used as a diagnostic marker and also as a possible marker for treatment monitoring. These promising results need to be evaluated within a larger patient cohort.